ANALISA SPK DENGAN METODE AHP DALAM MENENTUKAN FAKTOR KONSUMEN DALAM MELAKUKAN KREDIT BARANG - Kiki Fatmawati; Agus Perdana Windarto; Solikhun Solikhun; Muhammad Ridwan Lubis (STMIK Budi Darma, 2017)
Credit is a financial facility that allows a person or business entity to borrow money to purchase the product and repay it within the specified time period. UU No.10 of 1998 states that credit is the provision of money or bills that can be equalized, based on the agreement or lending and borrowing agreements between banks with other parties that require the borrower to repay his debt after a certain period of time with the giving of interest. Currently, credit facilities become the main source of consumer financing in buying goods. In addition there are also consumers who are classified as having enough income to purchase in cash, but choose on credit because there are other needs that must be met. Associated with the cost of most consumers make purchases on credit are consumers who are classified as having middle class income. The process of giving credit to consumers is not easy, because it must consider various factors. The purpose of this research is to make decision support system in determining consumer factor in doing credit goods. Case study conducted by researchers is PT. ADIRA Dinamika Multi Finance Tbk pematangsiantar branch. The method used in this research is Analitycal Hierarchy Process (AHP) method that can give the best ranking order. So as to produce criteria with the highest weights that can be used as consideration for decision makers to be used in decision making. It is expected that this research can contribute to the company in assessing the biggest factor of consumers in choosing goods credits.